A Review on Prosopis cineraria (L.) - Ms. Pallavi Maruti Patil; Dr. Vanita G. Kanase (International Journal of Pharma and Bio Sciences, 2021)
Prosopis cineraria, belonging to the family Fabaceae is one of the boon plants of Western Rajasthan gives valuable natural possessions to the people. This tree is also a mythological important icon in local communities and recognized as a State symbol tree of Rajasthan. It includes 44 species and is considered among the world’s most damaging invasive species. Different components of genus Prosopis cineraria like leaves, pods, flowers, stem and seeds was selected for phytochemical screening to spot the various categories of metabolites. Leaves of this tree are used as animal fodder and its young pods used as vegetable. As this plant grows in water stress (or deficient area), antioxidant potential of pods has also been interrogated. Acetone and methanol extracts of Sangri pods are the most dominant bioactive extracts. Nutritional analysis shows it’s a good source of proteins and minerals like calcium, sodium and potassium. Pharmacological activities like analgesic, antipyretic, antihyperglycemic, antioxidant, anticonvulsant, anticancer, apoptotic and antimicrobial activities have been reported from plant extracts. The qualitative chemical analysis of extracts was achieved and established to be positive for alkaloids, proteins, carbohydrates, flavonoids, saponins and tannins in 50% ethanolic and aqueous solvent extracts of ratio 1:2. The premise is to summarize the ongoing studies on up-to-date and extensive information available regarding the therapeutic activities published in scientific journals and to provide a tabulated data in such a way that it is useful for academic investigator. This review is helpful in utilizing abridged scientific knowledge of the P. cineraria (L.), its phytoconstituents and pharmacological actions highlighting bioactive potential of the plant.